Analisis Sebaran Sapi Potong Hasil Kawin Suntik di Kabupaten Grobogan Menggunakan Sistem Informasi Geografis (SIG) - Irfan Maiyola; Bambang Agus Herlambang; Khoiriya Latifa (CV. ALIM'SPUBLISHING, 2024)
This research analyzes the distribution of artificially inseminated beef cattle across various districts in Grobogan Regency through WebGIS. The data reveals variations in the number of beef cattle per district, with Wirosari District having the highest population reaching 8,277 heads. The utilization of WebGIS provides advantages in information presentation, particularly with pop-up features when placing the cursor on specific regions, facilitating a profound understanding of the traders' distribution at the local level. This advantage offers significant benefits to stakeholders, including local governments and farmers in each district of Grobogan Regency. This analysis not only presents information visually but also opens opportunities for exploration and more accurate decision-making through the WebGIS platform, supporting efforts in sustainable management and development of the livestock sector.